PREPARASI DAN KARAKTERISASI ARANG DARI AMPAS SAGU SEBAGAI ADSORBEN DALAM MENURUNKAN KADAR COD DAN BOD LIMBAH CAIR PABRIK TAHU - Victor Kayadoe; Sunarti Sunarti; Yeslia Utubira; Nova Kayadoe (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2020)
The preparation and characterization of charcoal from sago pulp as an adsorbent in reducing content of COD and BOD of tofu factory waste has been carried out. Sago pulp has been turned into charcoal through carbonization at 400oC for 2 hours. The results of charcoal characterization using XRD show that the carbon produced from sago pulp carbonization has a low crystallinity which is indicated by a wide peak at around 2Î¸ 23oC, which is the characteristic carbon peak. The results of characterization using Surface Area Analyzer show that the pores in the sago pulp charcoal are very few and irregular, and dominated by macropores. The results of the characterization using SEM showed that sago pulp charcoal had very few pores. The material is dominated by the residue from the results of non-porous carbonization. Performance as an adsorbent to reduce the content of COD and BOD in tofu mill wastewater by batch method shows the capacity and efficiency of adsorption on COD of 75.00 mg/g and 35.21%, respectively. While capacity and efficiency of adsorption on COD of 7.00 mg / g and 3.57%, respectively